Thai Household Savings Ability Comparing between Formal and Informal Workers: ความสามารถในการออมของครัวเรือนไทยเปรียบเทียบระหว่างแรงงานในระบบ และแรงงานนอกระบบ - Vansuriya, Atipan; Hengpatana, Suwimon (Journal of Applied Economics and Management Strategy, 2019)
บทคัดย่อ บทความนี้มีวัตถุประสงค์เพื่อนำเสนอสถานการณ์การออมของครัวเรือนไทยโดยเปรียบเทียบระหว่างครัวเรือนที่ทำงานในระบบกับครัวเรือนที่ทำงานนอกระบบ และศึกษาความสามารถในการออมของครัวเรือนไทย โดยใช้ข้อมูลการสำรวจภาวะเศรษฐกิจและสังคมของครัวเรือน ปี 2560 จากสำนักงานสถิติแห่งชาติ กลุ่มตัวอย่างคือหัวหน้าครัวเรือนที่มีอายุ 20 ปีถึง 85 ปี ผลการศึกษาพบว่าปัจจัยที่ส่งผลในทางบวกต่อความสามารถใน การออมของครัวเรือนได้แก่ อายุ สถานภาพสมรสโสด รายได้เฉลี่ยของครัวเรือน จำนวนผู้พิการในครัวเรือน จำนวนสมาชิกในครัวเรือนที่ทำงานรับค่าจ้างและเงินเดือน ปัจจัยที่ส่งผลในทางลบต่อความสามารถในการออมของครัวเรือนได้แก่ จำนวนเด็กในครอบครัวที่อายุต่ำกว่า 15 ปี การทำงานในภาคการเกษตร การเป็นหนี้ และการเป็นเจ้าของบ้านและที่ดิน ความสามารถในการออมของครัวเรือนสามารถเพิ่มขึ้นได้หากครัวเรือนมีรายได้เพิ่มขึ้น ครัวเรือนจึงจำเป็นต้องลดรายจ่ายและหนี้สินของครัวเรือนเพื่อให้มีรายได้เหลือสำหรับออม รัฐบาลควรออกมาตรการทางการคลังเพื่อเพิ่มรายได้แก่ครัวเรือนที่มีเด็กอายุต่ำกว่า 15 ปีนอกจากนโยบายเรียนฟรี 15 ปี ที่มีอยู่เพื่อช่วยบรรเทาค่าครองชีพ นโยบายการคืนภาษีมูลค่าเพิ่ม (VAT) ให้กับครัวเรือนที่มีเด็กอายุต่ำกว่า 15 ปี ในการซื้อสินค้าและบริการ โดยมีการกำหนดวงเงินการซื้อสูงสุดต่อเดือน นอกจากนี้รัฐบาลควรส่งเสริมให้แรงงานนอกระบบออมในกองทุนการออมแห่งชาติเพื่อกระตุ้นให้เกิดการออมของคนกลุ่มนี้ คำสำคัญ: การออมของครัวเรือน แรงงานในระบบ แรงงานนอกระบบ ABSTRACT This article presents the savings situation of Thai households by comparing workers in the formal and informal sectors. The study of the savings ability of Thai households used data from the Household Socio-Economic Survey 2017 conducted by the National Statistical Office of Thailand. The observations were made by heads of households aged 20 to 85 years. The results indicated that demographic variables such as age, marital status, the number of disabled people in the household, the earners in the household, and socioeconomic variables such as household income, positively affected the ability of the household to save money. Other variables such as the number of children under 15 years of age, heads that worked in agriculture, and landowners negatively affected the ability of the household to save money. The study revealed that the ability to save can be increased if the income of the household increases. Households have to reduce their expenditure and household debt so that they have a residual income to save. Further, the government should issue fiscal measures in order to increase the income of households with children under 15 years of age in addition to the 15-year free education policy in order to alleviate their cost of living. Additionally, the VAT refund policy should be applied to households with children under 15 years for the spending of food and services with a limited amount per month. Moreover, the government should promote the National Savings Fund for informal workers in order to stimulate their saving ability. Keywords: Household Saving, Formal Workers, Informal Workers